Cytotoxic effect of Artesunate on myeloid leukemia cell lines through up-regulating miR-29c expression - Dou, Cui-Yun; Liu, Lu-Lu; Li, Feng; Liu, Lei; Wang, Cui-Ling; Wang, Li-Na; Wang, Hai-Hua; Zhang, Hao; Chen, Ming-Tai (Translational Cancer Research; Vol 7, No 6 (December 30, 2018): Translational Cancer Research, 2018)
Acute myeloid leukemia (AML) is a malignant hematopoietic neoplasm characterized by arrest of myeloid differentiation, rapid growth and apoptotic repression of leukemic blasts that arise from the hematopoietic stem/progenitor cell (HSPC) population within the bone marrow (BM) (1). In the past three decades, great progress has been made in understanding AML pathogenesis and clinical treatment with allogeneic stem cell transplantation (2). However, the current AML therapeutic regimen only cures ~20% of the patients (3), highlighting the urgent necessity for discovery and development of innovative agents and novel therapeutic strategies to improve present situation of AML treatment.